ANALYSIS OF UNDERSTANDING AND APPLICATION OF FIQH MUAMALAH (BAI’) AT TANAH ABANG MARKET TRADERS BLOCK B WITH PHENOMENOLOGY APPROACH - Abdian Fredy Wijaya; Erwandi Tarmidzi; Achmad Firdaus (Department Islamic Economics, 2022)
Purpose – To analyze the understanding and application of fiqh muamalah at Tanah Abang Market Traders Block B. Design/methodology/approach – The method in this research is Qualitative research methods with a phenomenological approach with nine respondents. Findings – The results of the research in this study are 88% do not understand but apply and 11% understand and apply in the pillars of bai, 83% understand and apply 17% do not understand and do not apply to the theme of valid bai requirements, 100% do not understand and apply to the qadbh theme, 66% understand and apply 33% do not understand and do not apply to the theme of khiar, 94% understand and do not apply 6% do not understand and do not apply to the theme of usury, 81% understand and do not apply 19% do not understand and do not apply to the theme of gharar, 100% understand and do not apply to the theme of dzalim Research limitations/implications – The scope used in the study only covers places that are not too large and broad in scope, and this study only uses 2 variables. The pandemic conditions hampered the research process, so that when the interview process the results were not optimal. Originality/value – The results of the research can be used as a basis for reference for educational institutions to actively provide socialization to traders, as well as religious institutions to be able to provide scientific studies on fiqh muamalah to market traders at Tanah Abang Block B. Keywords Fiqh Muamalah, Qualitative Research Bai’, Phenomenology Approach